The Effect of Government Spending, Labor, and Zis on Economic Growth in Indonesia with Per Capita Income as a Moderating Variable in 2018-2022 - Raid Ghaniyu Putra; Sofyan, Mochlasin (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2024)
This study aims to determine the Effect of Economic Growth, Labor, and ZIS on Economic Growth in Indonesia with Per Capita Income as a Moderation Variable in 2018-2022. This type of research is quantitative with secondary data from the official websites of BPS and BAZNAS. The data used in the study is monthly time series data from 2018-2022. The population of this study is Indonesia, with sample data collected using the saturated sampling method. The analysis methods used include descriptive statistical tests, stationarity tests, regression tests, T-tests, F tests, R2 tests, classical assumption tests, and Moderated Regression Analysis (MRA) tests. The analysis tool uses Eviews. Based on the study's results, it is shown that government expenditure has a positive and significant effect on economic growth, labor has a negative and significant effect on economic growth, and ZIS has a positive and significant effect on economic growth. At the same time, per capita income can moderate the influence of government and labor expenditure on economic growth. In contrast, per capita income cannot moderate ZIS on economic growth in Indonesia